Single‐exposure X‐ray phase imaging microscopy with a grating interferometer. (15th March 2022) - Wolf, Andreas; Akstaller, Bernhard; Cipiccia, Silvia; Flenner, Silja; Hagemann, Johannes; Ludwig, Veronika; Meyer, Pascal; Schropp, Andreas; Schuster, Max; Seifert, Maria; Weule, Mareike; Michel, Thilo; et al.
Abstract : This work presents and extends the single‐exposure phase imaging capabilities of X‐ray grating interferometry as demonstrated by an implementation at beamline I13‐1 of the Diamond Light Source. The results are especially relevant for future single‐pulse imaging experiments at X‐ray free‐electron lasers. Abstract : The advent of hard X‐ray free‐electron lasers enables nanoscopic X‐ray imaging with sub‐picosecond temporal resolution. X‐ray grating interferometry offers a phase‐sensitive full‐field imaging technique where the phase retrieval can be carried out from a single exposure alone. Thus, the method is attractive for imaging applications at X‐ray free‐electron lasers where intrinsic pulse‐to‐pulse fluctuations pose a major challenge. In this work, the single‐exposure phase imaging capabilities of grating interferometry are characterized by an implementation at the I13‐1 beamline of Diamond Light Source (Oxfordshire, UK). For comparison purposes, propagation‐based phase contrast imaging was also performed at the same instrument. The characterization is carried out in terms of the quantitativeness and the contrast‐to‐noise ratio of the phase reconstructions as well as via the achievable spatial resolution. By using a statistical image reconstruction scheme, previous limitations of grating interferometry regarding the spatial resolution can be mitigated as well as the experimental applicability of the technique.